Dampak Kesehatan Mental Broken Home terhadap Hasil Belajar Pendidikan Agama Islam pada Siswa - Santoso, Aura Putri (Sekolah Tinggi Ilmu Tarbiyah Insan Kamil Bogor, 2024)
Family is the main foundation in student development. In reality, not all children can get a good family environment. Children who get a bad environment can be obtained from a broken home. Poor family environment conditions will affect the mental health conditions of children as students. Mental health conditions that are disturbed due to broken homes can make student obstacles in learning, one of which affects student learning outcomes, one of which is in PAI subjects. This study aims to determine the broken home problems experienced by students and the impact of broken home mental health on student PAI learning outcomes. This research uses descriptive qualitative research methods through literature studies and questionnaires, in order to obtain concrete data in accordance with the research objectives. The object of research is high school teenage students who experience broken homes. From the results of the research data analysis, it is known that broken home students experience learning difficulties so that they experience a decrease and stuck on the learning outcomes of PAI subjects.